Perception of the Involvement of FKAAB UTHM Female Graduates in the Construction Sector From the Aspects of External and Internal Factors - Ayob, Nuramanina; Nur Syamimi Mohd Razali (Research and Innovation in Technical and Vocational Education and Training, 2025)
Issues concerning women’s participation in the construction industry remain relevant, particularly among engineering graduates entering the workforce. The construction sector is widely perceived as male-dominated and associated with physically and mentally demanding work environments. These perceptions can negatively influence female graduates’ interest in pursuing careers in the field. This study aims to examine the perceptions of female graduates from the Faculty of Civil and Built Environment Engineering (FKAAB) regarding their potential involvement in the construction industry. The analysis considers both external and internal influencing factors. External factors include salary prospects, work environment and the availability of training and mentorship. Internal factors involve family support, levels of stress and fatigue and self-efficacy in facing workplace challenges. A quantitative research approach was employed, involving a survey of 298 FKAAB female graduates who completed their studies between 2020 and 2024. Data were collected using structured questionnaires and analyzed through descriptive and inferential statistics using SPSS version 27. Findings from the descriptive analysis indicate that both external and internal factors significantly influence female graduates’ inclination to join the construction sector. Pearson correlation analysis further reveals a significant relationship between these two categories of factors. Overall, the study highlights the importance of balancing material support and psychological resilience in enhancing women’s confidence to participate actively in the construction industry. It is recommended that both industry stakeholders and higher education institutions adopt more holistic and supportive strategies to strengthen women’s engagement in this sector.